A PRELIMINARY NOTE ON THE EXPRESSIVE USES OF AFFIRMATIVE AND NEGATIVE PARTICLES IN ITALIAN AND ENGLISH - Giorgi, Alessandra (Armenian Folia Anglistika, 2025)
This work examines the properties of affirmative and negative particles, such as yes and no, when used to express emotions like regret, surprise, disapproval, and others. In the cases discussed here, yes and no do not negate or affirm the truth of the previous statement but instead convey the speaker’s emotional response to a certain content. They therefore belong to the category of expressive language, which transmits emotional meanings. This article compares Italian and English and argues that both languages in these cases use similar structures to express the speaker’s reactions, with specific intonation and gestures enhancing their expressive effect. This discussion will also demonstrate that pragmatic considerations can be integrated into a model of language to generate relevant expressive interpretations, framing language as a multimodal system.